2023
DOI: 10.3390/reports6010012
|View full text |Cite
|
Sign up to set email alerts
|

The Durability and Efficacy of Cryopreserved Human Umbilical Cord Tissue Allograft for the Supplementation of Cartilage Defects Associated with the Sacroiliac Joint: A Case Series

Abstract: This Institutional Review Board (IRB)-approved retrospective observational protocol aims to report the safety and efficacy of birth tissue allografts applied in 38 patients with treatment-resistant sacroiliac (SI) joint pain. The research methodology consisted of an observational recording of the Numeric Pain Rating Scale (NPRS) and the Western Ontario and McMaster Universities Arthritis Index (WOMAC), which measure pain, stiffness, and physical function. No adverse events or adverse reactions were observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…These findings are consistent with the results of a knee osteoarthritis study in 2020, in which a total of 34 out of 42 patients reported significant clinical improvement [18]. A sacroiliac joint study in 2022 reported 32 of 38 patients with a lowered NPRS, and 29 of 38 patients reported a lowered WOMAC score [17]. In addition to the structural collagen matrix of WJ, the growth factors, cytokines, proteoglycans, and hyaluronic acid may be positive contributing factors to its success as a tissue transplant [16].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings are consistent with the results of a knee osteoarthritis study in 2020, in which a total of 34 out of 42 patients reported significant clinical improvement [18]. A sacroiliac joint study in 2022 reported 32 of 38 patients with a lowered NPRS, and 29 of 38 patients reported a lowered WOMAC score [17]. In addition to the structural collagen matrix of WJ, the growth factors, cytokines, proteoglycans, and hyaluronic acid may be positive contributing factors to its success as a tissue transplant [16].…”
Section: Discussionsupporting
confidence: 88%
“…WJ has shown promising results in the application to defects of the sacroiliac (SI) joint. When WJ was applied to the SI joint, there were statistically significant improvements in function, joint mobility, and pain relief [17]. In addition, when WJ was applied to the knee, data were analyzed to show pain alleviation, function improvement, and a potential delay in total knee replacement in patients with knee osteoarthritis [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of the survey being non-blinded is minimized by using patient-reported scales of NPRS and WOMAC, which quantize patient pain, functionality, and stiffness based on an array of questions. The positive results presented in this retrospective case series align with current literature on human tissue defects associated with knee osteoarthritis (Davis, 2022), articular cartilage defects affiliated with the sacroiliac joint (Lai, 2023), degenerative tissue in sacral decubitus ulcers (Lavor, 2023), and more. Patient-reported pain, joint stiffness, and physical function had a 20.52% improvement in the knee study by Davis, an 84% reduction in NPRS, and a 76% reduction in WOMAC in the sacroiliac joint study by Lai.…”
Section: Discussionsupporting
confidence: 83%
“…The positive results presented in this retrospective case series align with current literature on human tissue defects associated with knee pain and articular cartilage defects affiliated with the sacroiliac joint [15,16]. Patient-reported pain, joint stiffness, and physical function had a significant improvement in the knee study by Timmons.…”
Section: Discussionsupporting
confidence: 79%